Keutamaan Membaca Al-Qur’an Menurut Al-Qur’an dan Hadis - Heriman, Muhammad; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The importance of reading the Koran is a major aspect of Muslim religious practice. The Qur'an, as the holy book revealed to the Prophet Muhammad SAW, has virtues that are explained in the text itself and in the hadiths of the Prophet. This research aims to investigate the virtues of reading the Qur'an according to the Qur'an and Hadith In the context of the Qur'an, there are verses that emphasize the importance of reading, understanding and contemplating the meaning of Allah's verses. These verses provide guidance for Muslims to gain wisdom, life guidance, and blessings through reading and understanding the Al-Qur'an. Apart from that, the Qur'an also mentions that people who diligently read the Qur'an will get rewards and blessings in this world and the hereafter. The hadith of the Prophet Muhammad SAW also emphasizes the virtue of reading the Koran. The Prophet said that every letter of the Koran read by a Muslim will bring a reward, and each reward will be multiplied in the reading of the Koran. Other hadiths highlight the spiritual benefits and blessings gained through active engagement in reading and understanding the Qur'an. This research also discusses recommended ways to read the Qur'an with full khushu' (solemn) and tuma'ninah (calm). This includes understanding the meaning of verses, reflecting on Islamic teachings, and practicing the moral values ​​contained in the Koran. By detailing the virtues of reading the Qur'an through analysis of the Qur'an and Hadith, this research seeks to provide a deeper understanding of how important the activity of reading the Qur'an is in the life of a Muslim. It is hoped that the conclusions of this research can provide motivation and inspiration to Muslims to be more diligent in reading and contemplating the meaning of the Al-Qur'an in an effort to get closer to Allah SWT.